Design and analysis of a high-power radial multi-way combiner. Issue 1 (16th October 2013) - Jain, Akhilesh; Gupta, Alok K.; Sharma, Deepak Kumar; Hannurkar, Pundlik Rama; Pathak, Surya Kant
Abstract : In this paper, the design analysis of a multi-way and high-power radial combiner is presented. This combiner incorporates a rigid stripline-type combining structure. This analysis, based on an equivalent circuit model and segmentation of the radial transmission line, provides simple design formulae. The developed methodology, after fine-tuning with the help of an electromagnetic full-wave simulator, is physically demonstrated by developing a high-power (16 kW average) and high combining-efficiency (98.9%) 16-way combiner at the center frequency of 505.8 MHz. Its efficient and repeatable performance, fabrication-friendly structure, and absence of the heat-related problem, caused by the isolation resistor, are the main features of this design.